Management of oligometastatic rectal cancer: is liver first? - Mitin, Timur; Enestvedt, C. Kristian; Thomas Jr, Charles R. (Journal of Gastrointestinal Oncology; Vol 6, No 2 (April 13, 2015): Journal of Gastrointestinal Oncology, 2014)
Twenty percent of patients with rectal cancer present with synchronous liver metastases at the time of initial diagnosis. These patients can be treated with a curative intent, although the choice and sequence of treatment modalities are not well established and are commonly debated in multi-disciplinary tumor boards. In this article we review clinical evidence for various treatment approaches and attempt to formulate a pathway for clinicians to use in evaluating and managing these patients.